A technique for selecting potato (Solanum tuberosum) genotypes with low nitrogen requirement - GOVINDAKRISHNAN, P M; SHARMA, R C; KHAN, I A; SHARMA, H C (The Indian Journal of Agricultural Sciences, 2013)
The technique consists of fitting the quadratic model to find relationship between yield of a genotype and N rates, followed by determination ofN dose for getting maximum yields of each genotype including the standard cultivar. The maximum yield of standard cultivar is termed as fixed yield target. The dose of N for achieving the fixed yield target by a genotype is determined and genotypes requiring less N than standard cultivar are designated as low-nitrogen requiring genotypes. Methods were also developed to determine the relative and absolute ecofriendly indices of N of the genotypes compared to standard cultivars. Based on the technique, ’P1 376’ (’Kufri Ashoka’) was identified as low-N requiring early duration potato (Solanum tuberosum L.) genotype from the tuber yield data of the field experiments conducted at Modipuram from 1991-92 to 1993-94. It required 65 kg N/ha compared to 194 kg N/ha for ’Kufri Chandramukhi’ (standard cultivar) for attaining a fixed tuber yield target of 33.4 tonnes/ha. In the medium duration ’MS 78-46’ tequired 133 kg N/ha compared to 211 kg N/ha by ’Kufri Bahar’ (standard cultivar) for attaining yield target of 41.7 tonnes/ha. The ’MS 78-46’ and ’Kufri Ashoka’ were more ecofriendly as their relative and absolute ecofriendly indices were higher than the standard cultivars. ’Kufri Ashoka’ was more efficient in utillizing N from soil while ’MS 78-46’ was more efficient in utillizing N from soil as well as fertilizer source than the standard cultivars.